PENGARUH BERMAIN MENYORTIR ANGKA TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI TK DARUL FALAH SALO KABUPATEN KAMPAR. - Dewi Utari; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: based on the result of observation on the ability to recognize the concept of numbers of young learners has not developed optimally. So it is necessary to implement the activity play sorting numbers. The objective of this research is to find out the effect of play sorting numbers on the ability to recognize the concept of numbers of children age 5-6 years at TK Darul Falah Salo, Kampar regency. The sample used in this research are 15 young learners. The data collection technique used observation and documentation. The data analysis technique used t-test and SPSS 20.0 program. The hyphothesis of the research is there an effect of play sorting numbers on the ability to recognize the concept of numbers on children age 5-6 years at TK Darul Falah Salo, Kampar regency. It can be seen by the result analysis of thitung= 8.216 and Sig. (2-tailed)= 0.000, because Sig (2-tailed)= 0.000< 0.05, it can be conclued that there is a significant effect on the ability to recognize the concept of numbers before and after conducting an experiment by applying play sorting numbers. The effect of play sorting numbers on the ability to recognize the concept of numbers on children age 5-6 years at TK Darul Falah Salo, Kampar regency are 30.405%.Key words: The Ability To Recognize The Concept Of Numbers, Play Sorting Numbers.